A propensity-score matched comparison of perioperative and early renal functional outcomes of robotic versus open partial nephrectomy. - Zhenjie Wu; Mingmin Li; Le Qu; Huamao Ye; Bing Liu; Qing Yang; Jing Sheng; Liang Xiao; Chen Lv; Bo Yang; Xu Gao; Xiaofeng Gao; et al. (PLoS ONE)
Objectives To compare the perioperative and early renal functional outcomes of RPN with OPN for kidney tumors. Materials and methods A total of 209 RPN or OPN patients with availability of preoperative cross-sectional imaging since 2009 at our center were included. To adjust for potential baseline confounders propensity-score matching was performed, which resulted in 94 OPNs matched to 51 RPNs. Perioperative and early renal functional outcomes were compared. Results In propensity-score matched analysis, RPN procedures were well tolerated and resulted in significant decreases in postoperative analgesic time (24 vs. 48 hr, p<0.001) and visual analog pain scale (3 vs. 4, p<0.001). Besides, the RPN patients had a significantly shorter LOS (9 vs. 11 days, p = 0.008) and less EBL (100 vs. 200 ml, p<0.001), but median operative time was significantly longer (229 vs. 182 min, p<0.001). Ischemia time, transfusion rates, complication rates, percentage eGFR decline and CKD upstaging were equivalent after RPN versus OPN. In multivariable logistic regression analysis, RPN patients were less likely to have a prolonged LOS (odds ratio [OR]: 0.409; p = 0.016), while more likely to experience a longer operative time (OR: 4.296; p = 0.001). However, the statistical significance for the protective effect of RPN versus OPN in EBL was not confirmed by examining the risk of EBL≥400 ml (OR: 0.488; p = 0.212). Conclusions When adjusted for potential selection biases, RPN offers comparable perioperative and early renal functional outcomes to those of OPN, with the added advantage of improved postoperative pain control and a shorter LOS.